Strategic Assessment of AIMS Students’ Learning Opportunities and Challenges During the New Normal - Giner, Rhogin V. (Future Science / FSH-PH Publications, 2023)
This study examines the learning opportunities and challenges faced by students at the Asian Institute of Maritime Studies (AIMS) in response to the sudden shift to online learning during the Covid-19 pandemic. AIMS, like many educational institutions in the Philippines, adapted to the new normal setting by implementing online learning with all its facets. While this setup opened up new opportunities for students, it also presented various challenges. The research involved 337 AIMS students from the 2021-2022 academic year, using a descriptive-comparative design to assess differences in opportunities gained and challenges experienced. The participants were selected through a combination of purposive and random sampling. Data was collected using a standardized instrument consisting of three parts: profiling respondents, determining opportunities gained using the